2017
DOI: 10.1063/1.4994631
|View full text |Cite
|
Sign up to set email alerts
|

A mode-coupling theory analysis of the observed diffusion anomaly in aqueous polyatomic ions

Abstract: In contrast to simple monatomic alkali and halide ions, complex polyatomic ions such as nitrate, acetate, nitrite, and chlorate have not been studied in any great detail. Experiments have shown that diffusion of polyatomic ions exhibits many remarkable anomalies; notable among them is the fact that polyatomic ions with similar size show large difference in their diffusivity values. This fact has drawn relatively little interest in scientific discussions. We show here that a mode-coupling theory can provide a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…A classical, and rather simple, model is the small‐step rotational diffusion model based on the Debye diffusion picture, in which the reorientation proceeds through a sequence of very small jumps. It was later on demonstrated that this picture is more applicable to the motion of macromolecules, but not that much to the water molecules (Bagchi, ; Banerjee & Bagchi, ; Laage, ; Laage & Hynes, ; Yamaguchi, Abe, & Nishiyama, ; Zasetsky, Petelina, Lyashchenko, & Lileev, ; Q. Zhang, Chen, et al, ; Q. Zhang, Wu, et al, ). A second picture is the so‐called “flickering cluster” mechanism (Eisenberg & Kauzmann, ), which assumes the formation of hydrogen bonds in water to be cooperative.…”
Section: Studying Water Reorientation Dynamics Based On the Theoreticmentioning
confidence: 99%
“…A classical, and rather simple, model is the small‐step rotational diffusion model based on the Debye diffusion picture, in which the reorientation proceeds through a sequence of very small jumps. It was later on demonstrated that this picture is more applicable to the motion of macromolecules, but not that much to the water molecules (Bagchi, ; Banerjee & Bagchi, ; Laage, ; Laage & Hynes, ; Yamaguchi, Abe, & Nishiyama, ; Zasetsky, Petelina, Lyashchenko, & Lileev, ; Q. Zhang, Chen, et al, ; Q. Zhang, Wu, et al, ). A second picture is the so‐called “flickering cluster” mechanism (Eisenberg & Kauzmann, ), which assumes the formation of hydrogen bonds in water to be cooperative.…”
Section: Studying Water Reorientation Dynamics Based On the Theoreticmentioning
confidence: 99%
“…Similar to viscosity, the friction on a tagged particle can be decomposed into a short- and a long-time part using the separation of time scales between the binary collision and the repeated collisions. The resulting expression of friction can be written as ζ ( z ) = ζ B ( z ) + ζ R ( z ) where ζ B ( z ) is the binary part of the friction and ζ R ( z ) is the long-time part of the friction that arises due to correlated recollisions of solute particles with solvent molecules. The expression for the binary part of the friction ζ B ( z ) is given somewhere else .…”
Section: Mode Coupling Theory (Mct) Approach To Shear Viscosity Of El...mentioning
confidence: 99%
“…R ρρ ( z ) and R TT ( z ) are obtained by the Laplace transformation of R ρρ ( t ) and R TT ( t ), respectively. The expressions for R ρρ ( t ) and R TT ( t ) are given as ,, R ρ ρ ( t ) = ρ k B T m [ normald k / ( 2 π ) 3 ] ( · ) 2 k 2 [ c 12 false( k false) ] 2 × false[ F s ( k , t ) F o ( k , t ) false] F false( k , t false) and R TT ( t ) = 1 ρ [ normald k / ( 2 π ) 3 ] [ 1 ( · ) 2 ] × false[ γ normald<...…”
Section: Mode Coupling Theory (Mct) Approach To Shear Viscosity Of El...mentioning
confidence: 99%
“…Dynamics of polyatomic ions have been studied both theoretically and computationally in a series of work. 13,59,80,83,84 All the ions we have discussed till now are monovalent and with a planar geometry. Now, there is a different class of molecules with fully symmetric charge distribution but in a tetrahedral geometry, such as sulfate (SO 4 2− ) and ammonium (NH 4 + ).…”
Section: Perspectivementioning
confidence: 99%
“…(d) A comparison of the simulation results with that of semiquantitative mode-coupling theory formalism for nitrate ions (q Oa /q Ob = 1) and four model ions (q Oa /q Ob ≠ 1) (taken from Ref. 83). q Oa /q Ob D MCT q Oa q Ob D MCT q Oa q Ob =1 D Simulation q Oa q Ob D Simulation q Oa q Ob =1 0.125 0.32 0.65 0.5 0.57 0.74 1.5 0.85 0.86 2.0 0.67 0.75…”
Section: Perspectivementioning
confidence: 99%